Desenvolvimento e avaliação biológica de hidrogel contendo nanocápsulas de óleo de romã e silibinina para o tratamento de danos inflamatórios cutâneos causados pela radiação ultravioleta - Marchiori, Marila Crivellaro Lay (2017)
Silibinin (SB) is a flavonoid extracted from the plant Silybum marianum that has been studied as an active substance to protect the skin against damage ultraviolet-induced. Its limited solubility and bioavailability impairs its biological effects on different tissues. Pomegranate (Punica granatum) oil (PO) is considered a potent natural antioxidant. The nanotechnology has provided numerous benefits such as: modulation of the skin permeation/penetration/retention of active substance and sustained release. Then, the purpose of this study was to develop, for the first time, nanocapsule with PO as the oil core for SB encapsulation (NCSB), to evaluate its in vitro antioxidant capacity, to verify its in vitro cytotoxicity in human lines, to incorporate the suspensions in gellan gum hydrogels, to evaluate its anti-inflammatory effect in a model of ear edema induced by UVB radiation in mice and to study the SB permeation in excised human skin. NCSB presented mean diameter of 160 nm, polydispersity index below 0.1, negative zeta potential, pH around 5.6, SB content close to the theoretical value (1 mg/mL) and encapsulation efficiency greater than 96 %. Similar results were obtained for the formulation without SB (NCPO). These characteristics were maintained for 30 days under storage at 4°C. The nanoencapsulation controlled the SB release at least 10 times when compared to the methanolic solution, fitting to a first-order kinetics. NCSB demonstrate antioxidant capacity statistically greater than the free SB. Cell viability (by MTT test), genotoxicity and protein carbonylation showed that the nanocapsule suspensions were non-toxic to human monocytes and lymphocytes. NCSB and SB did not cause cytotoxicity in keratinocytes, whereas NCPO caused a significant decrease in viability. Fibroblasts were more sensitive than keratinocytes to nanocapsules and free compounds presence. The hydrogels presented adequate pH value (5.6-5.9) and SB content around 1 mg/g. The in vitro release has demonstrated that nanocapsules decreased the SB retention in the semisolid formulation. The in vivo experiment demonstrated that the formulations containing SB or NCSB were effective in reducing mouse ear edema and leukocyte infiltration for 24 hours. After 48 hours, only hydrogels containing NCSB, NCPO or association between free SBPO demonstrated antiedemogenic effect, as well as the positive control (silver sulfadiazine 1% hydrogel). After 72 hours, the hydrogel containing NCPO still showed a small antiedemogenic activity. The hydrogel containing NCSB provided higher SB retention on the skin, especially in the stratum corneum and epidermis than the semisolid containing free SB. Thus, it can be concluded that the formulations developed are promising for the treatment of skin damage UVB-induced, to modulate the cutaneous SB distribution in the layers of interest and are safe for keratinocytes and blood mononuclear cells, which are toxicity biomarkers.